PENGARUH BEBERAPA JENIS PUPUK KANDANG DAN NPK TERHADAPPERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) - Siti Aisyah; Hapsoh Hapsoh; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Onion (Allium ascalonicum L.) is a horticultural commodity belonging to spice vegetables that have many benefits and high economic value.This study aims to examine the effect of interaction of several types of manure and NPK and to get the best treatment of the growth and onion result (Allium ascalonicum L.). The research was conducted at experimental garden of Agriculture Faculty of University of Riau, Campus of Bina Widya Km 12,5 Simpang Baru, Tampan Pekanbaru.The study was conducted four months from September to December 2016,conducted experimentally using Randomized Complete Design (RCD) Factorial comprises 2 factors. Factor 1 type of manure (P) 10 tonnes/ha (2 kg/ha) comprises 4 levels: without manure, cow manure, chicken manure, goat manure. Factor 2 dose NPK (N) comprises 3 levels: without NPK, NPK dose 37.5 g/line, dose NPK 75 g/line, from both factors obtained 12 combinations with 3 replications there were 36 experimental units. The parameters those observedwere plant height, leaf number, greatest tubers, tubers number, weight fresh tubers, and weight tuber are suitable to store.The results of the variance continued with Duncan Multiple Range Test at 5% level. The results showed the interaction of chicken manure and NPK dose significantly affected  plant height, leaf number, greatest tubers, tubers number, weight fresh tubers, and weight tuber are suitable to store.The best combination is in the treatment of chicken manure 10 tonnes/ha and 75 g/2m2 NPK fertilizer.  Keywords:Manure, NPK Fertilizer, Onion